Prologue to democratic dissent in America - Ivie, Robert L. (Javnost (Ljubljana), 2004)
This essay considers the problematic of dissent being rendered oxymoronic with democracy in the United States under conditions of a weak democratic culture and an aggressive prosecution of the war on terror. It examines obstacles to democratic dissent in the U.S. and potential resources for rehabilitating it, sketching a preliminary map of the theoretical and cultural ground to be covered in a resistance to the further militarization of global politics. Suggesting that democracy is dissent, and democratic dissent is rhetorical critique, the essay argues that extant political culture might be rearticulated to dissent by language critiques that produce persuasive re-descriptions and symbolic merging.
Keywords: United States of America; ZDA; civil society; civilna družba; država; state; authority; oblast; democracy; demokracija